Neuroendocrine and Metabolic Effects of Low-Calorie and Non-Calorie Sweeteners - Moriconi, Eleonora; Feraco, Alessandra; Marzolla, Vincenzo; Infante, Marco; Lombardo, Mauro; Fabbri, Andrea; Caprio, Massimiliano (Frontiers in Endocrinology, 2020)
Since excessive sugar consumption has been related to the development of chronic metabolic diseases prevalent in the Western world, the use of sweeteners has gradually increased worldwide over the last few years. Although low- and non-calorie sweeteners may represent a valuable tool to reduce calorie intake and prevent weight gain, studies investigating the safety and efficacy of these compounds in the short- and long-term period are scarce and controversial. Therefore, future studies will need to elucidate the potential beneficial and/or detrimental effects of different types of sweeteners on metabolic health (energy balance, appetite, body weight, cardiometabolic risk factors) in healthy subjects and patients with diabetes, obesity and metabolic syndrome. In this regard, the impact of different sweeteners on central nervous system, gut hormones and gut microbiota is important, given the strong implications that changes in such systems may have for human health. The aim of this narrative review is to summarize the current evidence for the neuroendocrine and metabolic effects of sweeteners, as well as their impact on gut microbiota. Finally, we briefly discuss the advantages of the use of sweeteners in the context of very-low calorie ketogenic diets.